Causal Effects of Blood Lipid Traits on Inflammatory Bowel Diseases: A Mendelian Randomization Study - Ziqin Yao; Feiyu Jiang; Hongbin Luo; Jiahui Zhou; Wanting Shi; Shoufang Xu; Yingying Zhang; Feng Dai; Xinran Li; Zhiwei Liu; Xinhui Wang (Metabolites, 2023)
Inflammatory bowel diseases (IBDs), including Crohn’s disease (CD) and ulcerative colitis (UC), have become a global health problem with a rapid growth of incidence in newly industrialized countries. Observational studies have recognized associations between blood lipid traits and IBDs, but the causality still remains unclear. To determine the causal effects of blood lipid traits, including triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) on IBDs, two-sample Mendelian randomization (MR) analyses were conducted using the summary-level genome-wide association study (GWAS) statistics of blood lipid traits and IBDs. Our univariable MR using multiplicative random-effect inverse-variance weight (IVW) method identified TC (OR: 0.674; 95% CI: 0.554, 0.820; p < 0.00625) and LDL-C (OR: 0.685; 95% CI: 0.546, 0.858; p < 0.00625) as protective factors of UC. The result of our multivariable MR analysis further provided suggestive evidence of the protective effect of TC on UC risk (OR: 0.147; 95% CI: 0.025, 0.883; p < 0.05). Finally, our MR-BMA analysis prioritized TG (MIP: 0.336; <semantics><mover accent="true">θ^</mover></semantics>MACE: −0.025; PP: 0.31; <semantics><mover accent="true">θ^</mover></semantics>λ: −0.072) and HDL-C (MIP: 0.254; <semantics><mover accent="true">θ^</mover></semantics>MACE: −0.011; PP: 0.232; <semantics><mover accent="true">θ^</mover></semantics>λ: −0.04) for CD and TC (MIP: 0.721; <semantics><mover accent="true">θ^</mover></semantics>MACE: −0.257; PP: 0.648; <semantics><mover accent="true">θ^</mover></semantics>λ: −0.356) and LDL-C (MIP: 0.31; <semantics><mover accent="true">θ^</mover></semantics>MACE: −0.095; PP: 0.256; <semantics><mover accent="true">θ^</mover></semantics>λ: −0.344) for UC as the top-ranked protective factors. In conclusion, the causal effect of TC for UC prevention was robust across all of our MR approaches, which provide the first evidence that genetically determined TC is causally associated with reduced risk of UC. The finding of this study provides important insights into the metabolic regulation of IBDs and potential metabolites targeting strategies for IBDs intervention.